An ameliorated two-stage randomized response model for estimating a rare stigmatized characteristic using Poisson distribution - G N Singh; Surbhi Suman (Kuwait Journal of Science)
The present work sheds light on the estimation procedure of mean number of per- sons bearing a rare sensitive characteristic utilizing Poisson distribution. A modied two-stage randomized response model for rare sensitive characteristics is used to acquire the truthful response and using these responses, unbiased estimators have been proposed for two situations based on the availability of the prior information on the supplementary rare non-sensitive characteristic. The variances and their estimates are derived for detailed study of the proposed estimators. The empirical studies are executed which show the superiority of the proposed estimators over contemporary estimators.